Towards an Agenda for Ecological Theology: An Intercontinental Dialogue - Conradie, Ernst M. (Journal for the Study of Religion, Nature and Culture, 2005)
This contribution to outline an agenda for (Christian) ecological theology includes a position paper from Ernst Conradie (Part 1). Responses to this position paper from Sigurd Bergmann, Robert Borrong, Steve Bouma-Prediger, Celia Deane-Drummond, Denis Edwards, William Everett, David Field, Samson Gitau, Jesse Mugambi and Peter Scott, form Part 2. There is also a rejoinder by Ernst Conradie. The paper identifies a number of issues that an ecological theology has to address in the fields of ethics and systematic theology (only). It calls for a proper theological rationale for Christian earthkeeping and seeks to avoid theological reductionism.Responses to this paper were invited from a somewhat random group of friends, colleagues and associates from all around the world. A rejoinder that offers a reply to these responses concludes this contribution.